The impact of health promotion training on university students’ health perceptions, healthy lifestyle behaviors, and risky behaviors - Çol, Bahar Kefel¡; Başaran, Ayşe Gümüşler; Köse, Burcu Genç (Frontiers in Psychology, 2024)
IntroductionUniversity period is a critical developmental stage in which health-related behaviors that will be effective throughout life are acquired. This study aims to to evaluate the effect of health promotion education given touniversity students on health perception, health behaviors and risky behaviors, to investigate the impact of the demographic characteristics of the participants on these three variables, and to investigate the potential relationship between the three variables.MethodsIt is a quasi-experimental study using a pre-post test design This study was conducted with 179 students. The Health Perception Scale, the Healthy Lifestyle Behaviors Scale, and the Risky Behaviors Scale were used to collect the data. A 7-week training program was implemented, and the post-training evaluation was made after 3 months. Percentage, mean, standard deviation, Mann–Whitney U, Kruskal-Wallis, Wilcoxon analysis, and Spearmen Correlation analysis were used to analyze the data.ResultsAfter health promotion training, it was determined that health perception and healthy lifestyle behaviors increased and risky behaviors decreased. A significant negative relationship was found between health perception after training and antisocial behavior, suicidal tendencies and dropping out of school. A significant negative relationship was found between healthy lifestyle habits and antisocial behavior, suicidal tendencies and school dropout. A positive significant relationship was determined between health perception and healthy lifestyle behaviors. The results of this study provide evidence of the effectiveness of training interventions in improving healthy lifestyle behaviors and health perception and reducing risky behaviors.DiscussionThe results support the planning of training programs to promote health on campuses. It also shows the effectiveness of training programs in preventing antisocial behavior, suicidal tendencies and school dropout.